Genetic diversity and patterns of population structure in Creole goats from the Americas. (17th January 2017) - Ginja, C.; Gama, L. T.; Martínez, A.; Sevane, N.; Martin‐Burriel, I.; Lanari, M. R.; Revidatti, M. A.; Aranguren‐Méndez, J. A.; Bedotti, D. O.; Ribeiro, M. N.; Sponenberg, P.; Aguirre, E. L.; et al.
Summary: Biodiversity studies are more efficient when large numbers of breeds belonging to several countries are involved, as they allow for an in‐depth analysis of the within‐ and between‐breed components of genetic diversity. A set of 21 microsatellites was used to investigate the genetic composition of 24 Creole goat breeds (910 animals) from 10 countries to estimate levels of genetic variability, infer population structure and understand genetic relationships among populations across the American continent. Three commercial transboundary breeds were included in the analyses to investigate admixture with Creole goats. Overall, the genetic diversity of Creole populations (mean number of alleles = 5.82 ± 1.14, observed heterozygosity = 0.585 ± 0.074) was moderate and slightly lower than what was detected in other studies with breeds from other regions. The Bayesian clustering analysis without prior information on source populations identified 22 breed clusters. Three groups comprised more than one population, namely from Brazil (Azul and Graúna; Moxotó and Repartida) and Argentina (Long and shorthair Chilluda, Pampeana Colorada and Angora‐type goat). Substructure was found in Criolla Paraguaya. When prior information on sample origin was considered, 92% of the individuals were assigned to the source population (threshold q ≥ 0.700). Creole breeds are well‐differentiated entities (mean coefficient of genetic differentiation = 0.111 ± 0.048, with the exception of isolated island populations). Dilution from admixture with commercial transboundary breeds appears to be negligible. Significant levels of inbreeding were detected (inbreeding coefficient > 0 in most Creole goat populations, P < 0.05). Our results provide a broad perspective on the extant genetic diversity of Creole goats, however further studies are needed to understand whether the observed geographical patterns of population structure may reflect the mode of goat colonization in the Americas.